Isolated central nervous system relapse in acute myeloid leukemia: a case report and review of therapeutic challenges - Burns, Colin; Muir, Ian; Foster, Jennifer; Emanuel, Anthony; Kochenderfer, Mark (Frontiers in Oncology, 2025)
Central nervous system (CNS) relapse in acute myeloid leukemia (AML) is an uncommon but clinically significant event, with isolated CNS involvement occurring in a minority of cases and often eluding standard surveillance protocols. We report the case of a 60-year-old man with biallelic CEBPA-mutated AML and complex cytogenetics who achieved two complete remissions over four years before developing isolated leptomeningeal relapse involving the cauda equina. Despite a favorable molecular profile, CSF analysis revealed more than 3,000 WBCs with 97% blasts in the absence of marrow disease. The patient was treated with intrathecal methotrexate, cytarabine, and hydrocortisone, and later transitioned to an Ommaya reservoir. His response was complicated by persistent neurologic deficits and treatment-related neurotoxicity, culminating in functional decline, disease progression in the CNS, and death under hospice care. This case underscores the diagnostic and therapeutic challenges of isolated CNS recurrence in AML, including limited intrathecal drug delivery to nerve roots, the lack of CSF molecular profiling, and the potential for clonal evolution. Given the poor prognosis and therapeutic resistance associated with such cases, our findings support the consideration of CSF surveillance and combined systemic-intrathecal therapy in high-risk patients, particularly those with monocytic subtypes, elevated LDH, or complex cytogenetics.